ARAH PEMBELAJARAN BAHASA ARAB PADA PONDOK PESANTREN DDI MANGKOSO BARRU DAN RAHMATUL ASRI MAROANGIN ENREKANG - Abdullah, Abdurrahman Wahid (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Traditional Islamic boarding schools are considered to teach Arabic as a tool to study classical Islamic texts (turats) for understanding their religion deeply. Whereas modern Islamic boarding schools perceive Arabic as a medium for communication, tasked with the reception and conveyance of ideas, knowledge, and information. This research took the form of field research, focusing on two research locations divided into two categories: traditional and modern. Data collection involved interviews, observations, and document analysis. Triangulation was applied in the data analysis stage. The research findings indicate that both typologies of Islamic boarding schools innovate and adapt without forsaking their distinctive characteristics, even though this might reduce the gap between them. In traditional Islamic boarding school DDI Mangkoso, the direction of Arabic language education emphasizes mastering grammar and morphology while also adopting language-oriented education. However, these schools face limitations that prevent them from achieving maximal results. On the other hand, the direction of Arabic language education in modern Islamic boarding school Rahmatul Asri focuses on mastering Arabic as a communication tool, following behaviorist theories, despite integrating nahwu-sharaf into its internal curriculum.